Pengaruh Model Pembelajaran Think Pair Share (TPS) terhadap Kemampuan Berpikir Kritis Peserta Didik dalam Konsep Al-Qur’an Hadits di Kelas VII Pondok Pesantren Diniyah Limo Jurai - Huda, Ahmad Nurul; Hasibuan, Pendi; Wati, Salmi; Mustafa, Mustafa (ALSYS, 2025)
The low level of critical thinking skills among students at Ponpes Diniyah Limo Jurai serves as the background for this study, which is attributed to the predominance of conventional teaching methods such as lectures and passive discussions. This study aims to examine the effectiveness of the cooperative learning model Think Pair Share (TPS) in improving students’ critical thinking abilities. A quasi-experimental method was employed using a posttest-only with nonequivalent groups design. A total of 52 seventh-grade students were randomly divided into two groups: experimental and control, each consisting of 26 students. Data were collected through questionnaires and documentation, and analyzed using normality and homogeneity tests, as well as hypothesis testing with the assistance of SPSS version 30. The results show a significance value (sig-2 tailed) of 0.038 < 0.05, indicating that the application of the TPS model has a significant effect on enhancing students’ critical thinking skills. This finding is supported by observation results showing noticeable improvement in critical thinking during the learning process. Thus, the TPS model is proven to be effective in improving students' critical thinking in Qur’an Hadits instruction. The study implies the need to adopt active learning models such as TPS in the context of Islamic boarding school education.